Catalytic efficient destruction of chlorobenzene and 1, 2-dichlorobenzene over La0.9Sr0.1MnO3 engineered by a scalable surface reconstruction strategy. (15th February 2023) - Li, Lu; Shi, Jianwen; Tian, Mingjiao; Zhao, Yaruo; Chai, Shouning; He, Chi
Graphical abstract: Highlights: Surface engineered La0.9 Sr0.1 MnO3 shows high activity to CB and o -DCB. o -DCB oxidation shows better water resistance and CO2 selectivity. Oxychlorination route is mainly occurred during CB degradation. Desorption process is the key route over o -DCB oxidation reaction. Reaction mechanisms of o -DCB and CB were proposed over prepared catalyst. Abstract: Catalytic deep destruction of chloroaromatic (CBzs) is still a tricky issue to be resolved due to inevitable catalyst deactivation and by-products generation. As potential precursors and model pollutants of toxic polychlorinated dibenzo-p-dioxins or dibenzofurans (PCDD/Fs), chlorobenzene (CB) and 1, 2-chlorobenzene ( o -DCB) are necessarily explored in the meantime within the same system to explore the systematic reachable capacity of catalysts. Here, we found that the surface reconstruction of LaMnO3 by partial substitution of La by Sr via diluted HNO3 etching is a promising strategy strengthening the interaction among Mn, La and Sr and promoting the exposure of active phase and therefore the catalyst reducibility, which combines the advantage of structural stability and chlorine tolerance of La-based perovskite, at the same time, a typical La terminated surface (which is low active) is solved by Mn cation exposure and induces in higher oxidation activity. Over which, 90 % of CB and o -DCB can be converted below 250 °C, far superior than those of Mn-based catalysts. o -DCB prefers higher humid atmosphere (15 vol % H2 O represents little negative effect on its catalytic activity) than CB due to higher chlorine substitution on benzene could consume more hydroxyl radical. Besides, the highest promotion efficiency occurs with the presence of 5 vol % H2 O for both CB and o -DCB. Even though a slightly poor generation of carbon oxides and inorganic chlorine products for o -DCB oxidation, the lowest CO formation is obtained during the testing temperature range. The differences in polychlorinated byproducts and residual Cl species on catalyst surface reveal that (oxy)chlorination is mainly occurred during CB oxidation but desorption route occupies that of o -DCB under 250 °C.